Interfacial metal-nitrogen units of NiCo/nitrogen-doped carbon for robust oxygen reduction reaction. (December 2019) - Gou, Wangyan; Bian, Jihong; Zhang, Mingkai; Xia, Zhaoming; Liu, Yuxuan; Yang, Yaodong; Dong, Qingchen; Li, Jiayuan; Qu, Yongquan
Abstract: Corrosion-induced nitrogen (N) leaching limits the long-term applications of N-doped carbon (NC) catalysts for electrocatalytic oxygen reduction reaction (ORR). Anchored N for NC can suppress their corrosion and thus restrain the loss of catalytically active sites, resulting in the improved ORR durability. Herein, we report our strategies to suppress the leaching of N by embedding the NiCo alloy nanoparticles in NC nanowires and thus creating the interfacial metal-N units (M-N) for the robust ORR durability in alkali over 50 h. Also, the synergistic effects of Ni/Co–N, abundant active sites and favourable kinetics bring the high ORR activity over the Pt/C benchmark. Thus, our strategies with the improved durability and activity could create promising ORR catalysts with ∼5 times of activity-durability factor over the NC catalysts. Graphical abstract: Image 1